Early ventilator liberation and decreased sedation needs after tracheostomy in patients with COVID-19 infection. Issue 1 (19th January 2021) - Carmichael, Heather; Wright, Franklin L; McIntyre, Robert C; Vogler, Thomas; Urban, Shane; Jolley, Sarah E; Burnham, Ellen L; Firth, Whitney; Velopulos, Catherine G; Idrovo, Juan Pablo
Abstract : Background: Since the outset of the coronavirus disease 2019 (COVID-19) pandemic, published tracheostomy guidelines have generally recommended deferral of the procedure beyond the initial weeks of intubation given high mortality as well as concerns about transmission of the infection to providers. It is unclear whether tracheostomy in patients with COVID-19 infection facilitates ventilator weaning, and long-term outcomes are not yet reported in the literature. Methods: This is a retrospective study of tracheostomy outcomes in patients with COVID-19 infection at a single-center academic tertiary referral intensive care unit. Patients underwent percutaneous tracheostomy at the bedside; the procedure was performed with limited staffing to reduce risk of disease transmission. Results: Between March 1 and June 30, 2020, a total of 206 patients with COVID-19 infection required mechanical ventilation and 26 underwent tracheostomy at a mean of 25±5 days after initial intubation. Overall, 81% of tracheostomy patients were liberated from the ventilator at a mean of 9±6 days postprocedure, and 54% were decannulated prior to hospital discharge at a mean of 21±10 days postprocedure. Sedation and pain medication requirements decreased significantly in the week after the procedure. In-hospital mortality was 15%. Among tracheostomy survivors, 68% were discharged to a facility. Discussion: The management of patients with COVID-19 related respiratory failure can be challenging due to prolonged ventilator dependency. In our initial experience, outcomes post-tracheostomy in this population are encouraging, with short time to liberation from the ventilator, a high rate of decannulation prior to hospital discharge, and similar mortality to tracheostomy performed for other indications. Barriers to weaning ventilation in this cohort may be high sedation needs and ventilator dyssynchrony. Level of evidence: Level V—Therapeutic/care management.